Optimisation of Delivery of the Ataxia Telangiectasia Mutated Transgene to HeLa Cells Using Glycosaminoglycan Enhanced Transduction - Siam, Ala'a (2021)
Ataxia telangiectasia (AT) is a monogenic syndrome that is characterised by hypersensitivity to ionising irradiation. This study is part of a proof-of-concept project for a non-viral gene therapy that utilises glycosaminoglycan-enhanced transduction (GET), which is based on transfection peptides that fuse membrane docking and cell penetrating domains. Previous work has demonstrated delivery of plasmid DNA (pDNA) encoding the AT-mutated gene (ATM) in vitro using the GET peptides FLR and FLH. The aim of this study is to optimise the GET formulation in vitro for delivery and expression of ATM pDNA in HeLa cells. Attempts were made to capture transgene expression via Zoanthus sp. green fluorescent protein (zsGreen) fluorescence and immunostaining, and to visualise results by flow cytometry and confocal microscopy. Results suggest that transfection efficiency may positively correlate with peptide : pDNA mass ratio (PDMR). They also suggest that the proteosome inhibitor MG132 may better stabilise ATM expression than the histone deacetylase inhibitor suberanilohydroxamic acid (SAHA). These results were found by flow cytometry for zsGreen fluorescence. Microscopic results due to experimental factors were inconsistent with those of flow cytometry, whereas immunostaining analysis was precluded by nonspecific binding of the secondary antibody. Further optimisation requires reproducing results for statistical analysis, validating ATM expression by immunostaining and microscopy, and replicating transfection results in ATM-/- fibroblasts. Future directions include establishing functionality of transfected ATM using irradiation assays, exploring effects of genomic integration on ATM expression, and developing formulations for in vivo performance using animal models.